Probabilistic determination of the ecological risk from OTNE in aquatic and terrestrial compartments based on US-wide monitoring data. (January 2017) - McDonough, Kathleen; Casteel, Kenneth; Zoller, Ann; Wehmeyer, Kenneth; Hulzebos, Etje; Rila, Jean-Paul; Salvito, Daniel; Federle, Thomas
Abstract: OTNE [1-(1, 2, 3, 4, 5, 6, 7, 8-octahydro-2, 3, 8, 8-tetramethyl-2-naphthyl)ethan-1-one; trade name Iso E Super] is a fragrance ingredient commonly used in consumer products which are disposed down the drain. This research measured effluent and sludge concentrations of OTNE at 44 US wastewater treatment plants (WWTP). The mean effluent and sludge concentrations were 0.69 ± 0.65 μg/L and 20.6 ± 33.8 mg/kg dw respectively. Distribution of OTNE effluent concentrations and dilution factors were used to predict surface water and sediment concentrations and distributions of OTNE sludge concentrations and loading rates were used to predict terrestrial concentrations. The 90th percentile concentration of OTNE in US WWTP mixing zones was predicted to be 0.04 and 0.85 μg/L under mean and 7Q10 low flow (lowest river flow occurring over a 7 day period every 10 years) conditions respectively. The 90th percentile sediment concentrations under mean and 7Q10 low flow conditions were predicted to be 0.081 and 1.6 mg/kg dw respectively. Based on current US sludge application practices, the 90th percentile OTNE terrestrial concentration was 1.38 mg/kg dw. The probability of OTNE concentrations being below the predicted no effect concentration (PNEC) for the aquatic and sediment compartments was greater than 99%. For the terrestrial compartment, the probability of OTNE concentrations being lower than the PNEC was 97% for current US sludge application practices. Based on the results of this study, OTNE concentrations in US WWTP effluent and sludge do not pose an ecological risk to aquatic, sediment and terrestrial organisms. Graphical abstract: Highlights: US-wide OTNE wastewater treatment plant effluent and sludge monitoring data. US-wide OTNE probabilistic risk assessment in WWTP mixing zones. US-wide OTNE probabilistic risk assessment in sludge amended soils. OTNE poses negligible risk to aquatic, sediment, and terrestrial dwelling organisms.